فن النشيد الإسلامي في تصور الحديث النبوي /THE CONCEPT OF THE PROPHET'S HADITH ON ISLAMIC NASYID ART - Pallawagau, Baso; Hafid, Erwin; Ahmad, La Ode Ismail; Rasna, Rasna (Jurnal Adabiyah, 2021)
صار لفظ النشيد الإسلامي لغة العصر، فالناس يحبون ويتداولون الأغاني الدينية من كبار السن حتى الأطفال فمن الضروري في العصر الحاضر أن يكون مفهوم فن النشيد من منظور إسلامي، حيث يصبح العديد من الناس عبيدًا لحرية لا يمكن أن يسيطر عليها الوعي الذاتي للإنسان، ويبدو أن الناس مغمورون في عالم الترفيه المفرط ويخالفون الحدود التي حددتها الشريعة الإسلامية، فأراد الباحثون أن يبينوا مفهوم النشيد، وموقف الحديث النبوي من النشيد، والآثار الحكمية للنشيد في الحديث النبوي. والمنهج المتبع في هذا البحث هو المنهج الوصفي الاستقرائي، وذلك بجمع الأحاديث المتعلقة بالغناء والموسيقى وهما جزء من النشيد. والطريقة المستخدمة لتحليل البيانات هي دراسة مكتبية وطريقة تحليلها وصفية. ونتيجة البحث تشير إلى أن مفهوم النشيد وأحكامه واختلاف العلماء فيه قد ورد في الأحاديث النبوية بيانه. وهذا البحث له آثار لفهم القيم الحقيقية للفن الإسلامي وخاصة لجيل المسلم الذي يواجه مشاكل الحياة الحديثة المعقدة، حتى يصبح جيلا متحضرا ومتأدبا.الكلمات المفتاحية: النشيد، الغناء، الموسيقى ABSTRACTIslamic Nasyid is a contemporary issue. People are increasingly liking and enjoying religious songs, from parents to children. In the modern era, the concept of art in an Islamic perspective is needed, where many humans become slaves to freedom that a human's self-awareness cannot control. Humans seem to be immersed in the world of excessive entertainment and violate the boundaries that the Shari'a has determined. Therefore, the author wants to explain the essence of nasyid art, the view of the Prophet's hadith on nasyid and the legal consequences of nasyid in the Prophet's hadith. This study is a literature review, classical and contemporary. The method used is a qualitative method with a descriptive approach by collecting hadiths related to songs and music as part of nasyid. For data processing, the methods used are library research and descriptive analysis methods. The study results indicate that the understanding of nasyid, the law and the differences between the scholars in it has been explained in the hadith of the Prophet. Therefore, this paper has implications for understanding the actual values of art, especially for the millennial Muslim generation who face complex modern life problems to become a civilized Muslim generation.